Distraction Osteogenesis in Cleidocranial Dysostosis: A Case Report - Ritthagol , Wipapun; Nuntanaranon, Thongchai (Thai Journal of Orthodontics, 2024)
Cleidocranial dysostosis is one of the congenital deformities that involved both teeth and their bone support. The deformities often present with complexity of disorder in the multiple regions. Base on the clinical evidence, the result of orthodontic treatment providing in the younger age groups revealed better outcome than in the older age patient groups. In addition, the treatment protocols are varied depend on the severity of deformities, age, developmental stage of the permanent dentition, periodontal status and budgets of treatment due to the long and multiple surgical operations. The orthodontic treatment protocol of cleidocranial dysplasia in the growing age could be started with the selected serial extraction of the deciduous teeth and removed the supernumerary teeth. This performance stimulates the spontaneous eruption of related permanent teeth to erupt in the alveolar bone with the proper position. The unerupted permanent teeth could only be achieved by artificial orthodontic force. The permanent dentition then will be aligned to get the optimal occlusion. Nevertheless, the surgical operation of jaw bones may be needed especially in patients with severe discrepancy of bony structures that beyond the orthodontic compensation. These guidelines of treatment provided the satisfied outcome of occlusion, masticatory function and facial esthetics in cleidocranial dysostosis patients.